Teaching 3D Computer Animation to Illustrators: The Instructor as Translator and Technical Director - Koning, W. F. (IEEE Computer Graphics and Applications)

Large-Scale Visualization Projects for Teaching Software Engineering - Müller, C.; Reina, G.; Burch, M.; Weiskopf, D. (IEEE Computer Graphics and Applications)

Visualization Curriculum Panel - or The Changes We Have Made to Our Visualization Courses Over the Last 10 Years - Domik, Gitta; Ebert, David; Kohlhammer, Jörn; Rushmeier, Holly; Santos, Beatriz Sousa; Weiskopf, Daniel (Eurographics 2012 - Education Papers)

Workflow-enhanced conformational analysis of guanidine zinc complexes via a science gateway - Herres-Pawlis, Sonja; Birkenheuer, Georg; Brinkmann, André; Gesing, Sandra; Grunzke, Richard; Jäkel, René; Kohlbacher, Oliver; Krüger, Jens; Dos Santos Vieira, Ines (Studies in Health Technology and Informatics)

Leveraging Multidisciplinarity in a Visual Analytics Graduate Course - Elmqvist, N.; Ebert, D. S. (IEEE Computer Graphics and Applications)

Digital Media and the Beginning Designer - Goldman, G. (IEEE Computer Graphics and Applications)

Fostering Collaboration and Self-Motivated Learning: Best Practices in a One-Semester Visualization Course - Domik, Gitta (IEEE Computer Graphics and Applications)

A Science Gateway Getting Ready for Serving the International Molecular Simulation Community - Gesing, Sandra; Herres-Pawlis, Sonja; Birkenheuer, Georg; Brinkmann, André; Grunzke, Richard; Kacsuk, Peter; Kohlbacher, Oliver; Kozlovszky, Miklos; Krüger, Jens; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; Steinke, Thomas (Proceedings of Science)

Tagungsbericht: Symposium für Promovierende der Fremdsprachen in der Endphase – \textquotedblEndspurt für Dis(s)orientierte\textquotedbl - Armbrust, Laura; Rumlich, Dominik (Zeitschrift für Fremdsprachenforschung)

The effects of CLIL: Students’ linguistic accuracy in relation to internal and external learner variables - Rumlich, Dominik (Language learning and language use)

(Sprach-)Tests in der Praxis: Die Studie „Development Of North Rhine-Westphalian CLIL Students“ (DENOCS). - Rumlich, Dominik (Fremdsprachenunterricht empirisch erforschen. Grundlagen - Methoden - Anwendung)

Long-Term ageing effects on Fused Deposition Modeling Parts manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (23rd Annual International Solid Freeform Fabrication Symposium)
Relating to the direct manufacturing of end-use parts the knowledge about the effect of the long-term ageing of Fused Deposition Modeling (FDM) parts is of particular importance. For this, tensile specimens were stored for time periods of up to 52 weeks in two different conditions and the testing was conducted at different temperatures within a temperature range of -60°C to +160°C. Further tests were made after the exposure in multiple media. The parts were built up with the system “Fortus 400mc” from Stratasys with the material Ultem*9085 in two different build directions, the strongest direction X (on its side) and the weakest build direction Z (upright) and with the standard toolpath parameters of the Insight software version 7.0.

The Bright and Dark Side of Endowed Status in Hierarchical Loyalty Programs - Eggert, A; Garnefeld, I; Steinhoff, L (2012 AMA Summer Marketing Educators' Proceedings)

I thought it was all over and now it is back again – Customer reactions to time extensions of sales promotions - Garnefeld, I; Münkhoff, E; Bruns, A (2012 AMA Summer Marketing Educators’ Proceedings)

Capturing the Value of Hybrid Offerings: The Impact of the Price Presentation Format - Eggert, A; Steiner, M; Ulaga, W; Backhaus, K (Proceedings of the 2012 ISBM Academic Workshop)

Dispersion of Market Activities: A Configurational Approach - Ritter, T; Eggert, A (Proceedings of the 2012 ISBM Academic Workshop)

Growing with Industrial Services - A Configurational Approach - Eggert, A; Münkhoff, E; Thiesbrummel, C (2012 AMA Winter Marketing Educators' Proceedings)

Endowed Status in Hierarchical Loyalty Programs - Eggert, A; Garnefeld, I; Steinhoff, L (2012 AMA Winter Marketing Educators' Proceedings)

Growing Existing Customers’ Profitability with Customer Referral Programs - Garnefeld, I; Helm, S; Eggert, A; Tax, S (2012 AMA Winter Marketing Educators' Proceedings)

Graph Transformation - 6th International Conference, ICGT 2012, Bremen, Germany, September 24-29, 2012, Proceedings